Equity valuation : Colgate Palmolive Co - Lopes, Carlos Miguel Rebola (2020)
The main purpose of this dissertation is to accomplish an accurate valuation of Colgate Palmolive Co, a consumer goods company, leader in the oral care market. In this thesis, two main valuation models were applied, the DCF method, using the FCFF, and the Relative Valuation model, which was used to have a better understanding of how the market evaluates companies similar to the one at study at this paper. Nonetheless, in order to have a better understanding of the main drivers regarding the company valuation, a sensitivity analysis was also performed. The final result is a Hold recommendation since the company is valuated at $68.58. To conclude was made a comparison between this thesis results and the results from the Deutsche Bank report of 26th July of 2019.